The anti-melanogenic properties of Swietenia macrophylla king - Camille, Keisha Mahendra; Ser, Hooi Leng *; Syafiq Asnawi, Zainal Abidin; Khan, Shafi Ullah; Priyia, Pusparajah; Htar, Thet Thet; Chuah, Lay Hong; Tang, Siah Ying; Long, Chiau Ming *; Goh, Khang Wen; Yatinesh, Kumari; Goh, Bey Hing * (Elsevier, 2023)
Fair flawless skin is the goal for some cultures and the development of irregular skin pigmentation is considered an indication of premature skin aging. Hence, there is a rising demand for skin whitening cosmetics. Thus, this research will be focusing on discovering the anti-pigmentation properties of Swietenia macrophylla seeds. Firstly, the seeds were extracted with ethanol and further fractionate based on their polarity before testing them on zebrafish embryos. The ethanolic extract of the seed demonstrated significant inhibition of both tyrosinase activity and melanin production in the embryos. However, after fractionation, the anti-melanogenic ability was observed to have decreased, signifying that the phytocompounds may be synergistic in nature. Still in the proteomic studies the ethanolic extract and its hexane fraction both induced the downregulation of cathepsin LB and cytoskeletal proteins that have connections to the melanogenic pathway, confirming that S. macrophylla seeds do indeed have anti-pigmentation properties that can be exploited for cosmetic use. Next, limonoids (tetranortriterpenoids found in the seed) were tested for their inhibitory effect against human tyrosinase related protein 1 (TYRP-1) via molecular docking. It was found that limonoids have a stronger binding affinity to TYRP-1 than kojic acid, suggesting that these phytocompounds may have the potential in inhibiting pigmentation. However, this still needs further confirmation before these phytocompounds can be developed into a skin whitening agent. Other assays like ex-vivo or 3D human skin culture can also be used to better study the seeds anti-pigmentation effect on humans.